2015
DOI: 10.5796/electrochemistry.83.846
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Dissolution of Lithium through Lithium Phosphorus Oxynitride Thin Film in Lithium Bis(trifluoromethylsulfonyl)amide-Glyme Solvate Ionic Liquid

Abstract: The deposition and dissolution of Li at a Ni electrode coated with lithium phosphorus oxynitride (LiPON) thin film were investigated in lithium bis(trifluoromethylsulfonyl)amide-glyme solvate ionic liquid. The LiPON thin film was able to suppress the irreversible decomposition of the solvate ionic liquid. The cathodic deposition of Li and anodic dissolution of the deposited Li occurred on the Ni electrode through the LiPON thin film. These results suggest that the LiPON thin film plays a role as an artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The broad and small reductive current that was observed during the first cycle might have resulted from the decomposition of [P 2225 ][TFSA] to form a solid electrolyte interphase (SEI) on the electrode. 51 Indeed, the reductive decomposition was suppressed during subsequent cycles, implying the formation of SEI passivation film on the electrode. We calculated the Coulombic efficiency from the CV results for both gel and solution systems (Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad and small reductive current that was observed during the first cycle might have resulted from the decomposition of [P 2225 ][TFSA] to form a solid electrolyte interphase (SEI) on the electrode. 51 Indeed, the reductive decomposition was suppressed during subsequent cycles, implying the formation of SEI passivation film on the electrode. We calculated the Coulombic efficiency from the CV results for both gel and solution systems (Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The CV behavior (i.e., Li deposition/dissolution reaction) seen in the ion gel was comparable to that in the corresponding solution system (Figure S1). The broad and small reductive current that was observed during the first cycle might have resulted from the decomposition of [P 2225 ]­[TFSA] to form a solid electrolyte interphase (SEI) on the electrode . Indeed, the reductive decomposition was suppressed during subsequent cycles, implying the formation of SEI passivation film on the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…We have been investigating the deposition and dissolution of metallic lithium using pyrrolidinium-based RTILs and solvated ionic liquids as electrolytes. 74,75 For example, we have shown that the use of lithium phosphorus oxynitride as an artificial solid electrolyte interphase on an electrode suppresses the reductive decomposition of the electrolyte and increases the Coulombic efficiency of the deposition and dissolution of metallic lithium in RTILs.…”
Section: Rtils As Electrolytes For Secondary Batteriesmentioning
confidence: 99%
“…Li metal having the theoretical specific capacity of 3861 mAh g ¹1 is also attractive to realize high specific capacity of the Li-S battery. Although fundamental studies on the electrochemical deposition and dissolution of Li have been reported so far, 14,15 there is no literature about the charge-discharge cycle of the Li anode in the LiTFSA-G4 solvate ionic liquid. It is well-known that the volumetric expansion associated with the whisker-like deposition of Li metal occurs during the charge process, leading to the short circuit of the cell in conventional electrolytes.…”
Section: Introductionmentioning
confidence: 99%